Working with the trauma of racism in groups in a time of white supremacy — erasure, psychic ghettoization or bearing witness. (June 2022) - Stevenson, Stuart
This article addresses the complex issues when working with group members who have been traumatized by institutional and inter-generational racism in the context of white supremacy. The article engages with how a group analytic understanding can assist clinicians to engage with group members who have experienced racial trauma and structural oppression when these dynamics are inevitably generated in psychotherapy groups. I discuss the concepts of 'erasure', 'bearing witness' and also introduce the concept of 'psychic ghettoization', which can provide the conductor with some conceptual tools to manage the complex issue of racial trauma. I argue that there is now more than ever a need to remain relevant to the diverse and often marginalized communities we serve. To do this requires group analysts and indeed all clinicians to urgently scrutinize and develop theories and techniques for working with racism in our practices and clinics. A lack of intervention equates to a by-standing and a complicit collusion with racism which risks a re-traumatizing dynamic being paralleled in our clinical work with group members from marginalized communities.